Minimisasi Dampak Limbah Domestik terhadap Kualitas Air Sungai - Rini Oki; Siti Nurhaliza; Riski Amelia Nasution (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Background: The direct discharge of domestic wastewater without prior treatment can degrade river water quality and disrupt the balance of aquatic ecosystems. The severity of these impacts varies across locations depending on population density and the intensity of activities surrounding the river basin. This condition has the potential to cause various adverse effects on both public health and the environment. Methods: This study employed a systematic literature review by collecting and analyzing 11 scientific articles, journals, and other relevant references concerning river water pollution caused by domestic wastewater. Results: The findings indicate that domestic wastewater has a significant impact on the deterioration of river water quality across all study locations, with pollution levels ranging from mild to moderate and tending to be more severe in densely populated downstream areas. Increased organic matter content resulted in higher Biological Oxygen Demand (BOD) and Chemical Oxygen Demand (COD) values, while Dissolved Oxygen (DO) levels decreased. In addition, the presence of pollution indicator bacteria, such as Total Coliform and Escherichia coli, increased due to the discharge of household wastewater into water bodies, accompanied by changes in water color, odor, and turbidity. Mitigation measures, including communal wastewater treatment plants (WWTPs), multi-stage filtration systems, and the utilization of microalgae, have been shown to significantly reduce pollutant loads when implemented consistently. However, their effectiveness remains limited to small-scale applications and has not yet covered all pollution sources.